PENGALAMAN KOMUNIKASI KELOMPOK USIA DEWASA DALAM KEKACAUAN INFORMASI SEPUTAR COVID-19 DI MEDIA SOSIAL - Afifah Azzahra; S. Rouli Manalu; Wiwid Noor Rakhmad (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
The Covid-19 pandemic phenomenon not only concerns the issues of a health crisis, but it has also resulted in a cascade of information, including facts and hoaxes, that is difficult to distinguish from one another and is easily shared through digital networks, one of which is social media. This situation, which is also known as information disorder, causes issues with the reception, processing, and interpretation of information that may vary from person to person. This study intends to acquire a thorough understanding of the subjective communication experiences of people in the adult age group when coping with the deluge of information concerning Covid-19 on social media. This research is qualitative research that uses an interpretive paradigm with an Interpretative Phenomenological Analysis (IPA) approach. The Elaboration Likelihood Model served as the study’s theoretical foundation. This research uses the concept of an echo chamber, filter bubble, and confirmation bias to show the characteristics of information about Covid-19 on social media due to the algorithm operating system. In-depth interviews with both male and female participants who met the age requirement of over 35 years old were employed as the method of data collection in this study, along with the usage of social media to address participants' information demands regarding Covid-19. The findings of this research indicate that individual interpretation and the type of response that is conveyed through behaviours and/or decision-making are impacted by subjective experience in handling various forms of information disorder concerning Covid-19 on social media. Some of the findings that reflect the communication relationship among participants in interpreting the disorder of information about Covid-19 on social media include (i) individuals in the adult age group consider WhatsApp as the main contributor to the conflicting information regarding Covid-19 on social media. (ii) People in the adult age group find it difficult to sort through the deluge of information regarding Covid-19 because they are unaware of the social media algorithm system. (iii) Possession of prior knowledge, be it false or true, related to Covid-19 makes information processing carried out by individuals in the adult age group biased. (iv) The lack of personal motivation to seek the correct information affects how much individuals in the adult age group can believe a certain piece of information during the disorder of information regarding Covid-19. (v) The disorder of information regarding Covid-19 has made individuals in the adult age group experience pandemic fatigue.